Manajemen Kesiapan Rantai Pasokan terhadap Gangguan Ekstrem pada Perusahaan - Ahmad Jet Alamin A; Parlaban Karo-Karo; Raliman Febby P. Purba S (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines supply chain readiness management in the face of extreme, system-wide disruptions such as natural disasters (e.g., Hurricane Maria) and geopolitical issues (trade wars, regional conflicts, protectionist policies, and economic sanctions). The research focuses on strategies and practices that enhance supply chain resilience so companies can continue operating, maintain production continuity, and reduce operational costs and risks. Using a qualitative approach with documentary analysis across multiple sources—including IBM and Resilinc references, as well as case study literature on building supply chain resilience—the study finds that readiness can be strengthened through data-driven demand planning using big data and predictive analytics, logistics process automation, and end-to-end visibility supported by technologies such as AI and IoT. Additionally, companies should implement integrated risk management (periodic evaluations and scenario simulations/stress testing), strengthen cross-stakeholder collaboration (suppliers, distributors, logistics partners), and reduce geopolitical exposure through supplier diversification via multi-sourcing and nearshoring